Pengaruh Sustainable Attitude Dan Perfectionist Attitude Terhadap Social Recommendation Use : (Studi Pada Konsumen Aplikasi Wisata Di Indonesia) - Naala Choirunni’mah; Muhammad As’ad (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study aims to examine the influence of sustainable attitude and perfectionist attitude on the use ofsocial recommendations among travel application users in Indonesia. Using a quantitative method andSEM-PLS analysis, data were collected from 301 Traveloka users. Results show that sustainable attitudehas a positive but small significant effect (path coefficient = 0.137; p = 0.040), while perfectionist attitudehas a strong positive and significant effect (path coefficient = 0.660; p = 0.001). These findings suggest thatperfectionist users heavily rely on social recommendations in travel decision-making. The results offervaluable insights for application developers and marketers to enhance user experience and supportsustainable tourism.Keywords: Sustainable Attitude, Perfectionist Attitude, Social Recommendation